2009
DOI: 10.1212/01.wnl.0000338630.20412.45
|View full text |Cite
|
Sign up to set email alerts
|

Role of MRI in the differentiation of ADEM from MS in children

Abstract: MRI diagnostic criteria are proposed that may be useful in differentiating children experiencing the first attack of multiple sclerosis from those with monophasic acute disseminated encephalomyelitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
127
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(138 citation statements)
references
References 14 publications
5
127
0
4
Order By: Relevance
“…Imaging abnormalities frequently resolve as the patient sustains clinical recovery [8,15,17,18]. Monophasic ADEM, at times, may be difficult to distinguish from the first attack of MS; however, MRI findings of diffuse, bilateral T2-hyperintense lesions in addition to absence of T1-hypointense Bblack holes^and lack of periventricular lesions weigh heavily in favor of a diagnosis of ADEM [23,24].…”
Section: Ademmentioning
confidence: 99%
“…Imaging abnormalities frequently resolve as the patient sustains clinical recovery [8,15,17,18]. Monophasic ADEM, at times, may be difficult to distinguish from the first attack of MS; however, MRI findings of diffuse, bilateral T2-hyperintense lesions in addition to absence of T1-hypointense Bblack holes^and lack of periventricular lesions weigh heavily in favor of a diagnosis of ADEM [23,24].…”
Section: Ademmentioning
confidence: 99%
“…Two of these 3 criteria were described to be sensitive for distinguishing MS from ADEM. 1 Subsequently, a large population-based study revealed that the highest odds ratio for subsequent MS diagnosis was the presence of both 1 periventricular T2-hyperintense lesion and at least 1 T1-hypointense lesion.…”
Section: Role Of Mri In Ms Diagnosismentioning
confidence: 99%
“…The French KIDMUS study showed that the presence of lesions perpendicular to the long axis of the corpus callosum and the sole presence of well-defined lesions had a sensitivity of 21%, specificity of 100%, positive predictive value (PPV) of 100%, and negative predictive value (NPV) of 61% for identification of MS. 17 The Callen et al 18 MS vs ADEM criteria demonstrated that the presence of 2 out of 3 of (1) absence of diffuse bilateral lesion pattern, (2) presence of black holes, or (3) presence of 2 or more lesions with periventricular lesions yielded a sensitivity of 81%, specificity of 95%, PPV of 95%, and NPV of 79% of identifying a child as having MS rather than ADEM. Verhey et al 19 demonstrated that the presence of $1 periventricular T2 bright lesion and $1 T1-hypointense lesion had a sensitivity of 84%, specificity of 93%, PPV of 76%, and NPV of 96% of identifying children with MS as compared to children with monophasic ADS.…”
Section: Mri Abnormalities Associated With Msmentioning
confidence: 99%